500-Gray γ-Irradiation May Increase Adhesion Strength of Lyophilized Cadaveric Split-Thickness Skin Graft to Wound Bed. (March 2017) - Wei, Lin-Gwei; Chen, Chieh-Feng; Wang, Chi-Hsien; Cheng, Ya-Chen; Li, Chun-Chang; Chiu, Wen-Kuan; Wang, Hsian-Jenn
Abstract : Background: Human cadaveric skin grafts are considered as the "gold standard" for temporary wound coverage because they provide a more conductive environment for natural wound healing. Lyophilization, packing, and terminal sterilization with gamma-ray can facilitate the application of cadaveric split-thickness skin grafts, but may alter the adhesion properties of the grafts. In a pilot study, we found that 500 Gy γ-irradiation seemed not to reduce the adherence between the grafts and wound beds. Aim and Objectives: We conducted this experiment to compare the adherences of lyophilized, 500-Gy γ-irradiated skin grafts to that of lyophilized, nonirradiated grafts. Materials and Methods: Pairs of wounds were created over the backs of Sprague- Dawley rats. Pairs of "lyophilized, 500-Gy γ-irradiated" and "lyophilized, nonirradiated" cadaveric split-thickness skin grafts were fixed to the wound beds. Adhesion strength between the grafts and the wound beds was measured and compared. Results: On post-skin-graft day 7 and day 10, the adhesion strength of γ-irradiated grafts was greater than that of the nonirradiated grafts. Conclusions: Because lyophilized cadaveric skin grafts can be vascularized and the collagen of its dermal component can be remodeled after grafting, the superior adhesion strength of 500-Gy γ-irradiated grafts can be explained by the collagen changes from irradiation.